Preoperative Screening and Case Cancellation in Cocaine-Abusing Veterans Scheduled for Elective Surgery - Nabil Elkassabany; Rebecca M. Speck; David Oslin; Mary Hawn; Khan Chaichana; John Sum-Ping; Jorge Sepulveda; Mary Whitley; Yasser Sakawi (Anesthesiology Research and Practice, 2013)
Background. Perioperative management of cocaine-abusing patients scheduled for elective surgery varies widely based on individual anecdotes and personal experience. Methods. Chiefs of the anesthesia departments in the Veterans Affairs (VA) health system were surveyed to estimate how often they encounter surgical patients with cocaine use. Respondents were asked about their screening criteria, timing of screening, action resulting from positive screening, and if they have a formal policy for management of these patients. Interest in the development of VA guidelines for the perioperative management of patients with a history of cocaine use was also queried. Results. 172 VA anesthesia departments’ chiefs were surveyed. Response rate was 62%. Over half of the facilities see cocaine-abusing patients at least once a week (52%). Two thirds of respondents canceled or delayed patients with a positive screen regardless of clinical symptoms. Only eleven facilities (10.6%) have a formal policy. The majority of facilities (80%) thought that having formal guidelines for perioperative management of cocaine-abusing patients would be helpful to some extent. Results. 172 VA anesthesia departments’ chiefs were surveyed. Response rate was 62%. Over half of the facilities see cocaine-abusing patients at least once a week (52%). Two thirds of respondents canceled or delayed patients with a positive screen regardless of clinical symptoms. Only eleven facilities (10.6%) have a formal policy. The majority of facilities (80%) thought that having formal guidelines for perioperative management of cocaine-abusing patients would be helpful to some extent. Conclusions. There is a general consensus that formal guidelines would be helpful. Further studies are needed to help formulate evidence-based guidelines for managing patients screening positive for cocaine prior to elective surgery.